Innovative methodology for comprehensive use of tin anode slime: Preparation of CaSnO3. (November 2019) - Liu, Wei; Gu, Kunhong; Han, Junwei; Ou, Zhenyu; Wu, Dixiu; Zhao, Deqiang; Qin, Wenqing
Graphical abstract: Highlights: Preparation of calcium stannate from tin anode slime was studied. More than 94% of tin was converted to calcium stannate by the proposed process. More than 99% As and 95% Sn could be extracted from tin anode slime. Abstract: Tin anode slime, a secondary resource containing Sn, was used as a raw material in the preparation of CaSnO3 via the processes of soda roasting, alkaline leaching, and precipitation. The effects of roasting, leaching, and precipitation on the extraction of tin from slime were investigated in detail. The following optimum conditions were identified: Na2 CO3 /tin anode slime mass ratio of 1:1, roasting temperature of 1000 °C, roasting time of 45 min, charcoal powder dosage of 20%, NaOH concentration of 2 mol/L, liquid-to-solid ratio of 14:1, leaching temperature of 65 °C, leaching time of 90 min, CaO/Sn mole ratio of 3.5:1, precipitation temperature of 85 °C, and precipitation time of 120 min. Under these conditions, more than 95% of Sn was extracted from tin anode slime after roasting and leaching, in which Sn was converted into Na2 SnO3, which enhanced Sn extraction. Furthermore, more than 99% of Sn was precipitated from the leach solution via the reaction with CaO. The proposed method exhibits advantages of low pollution, low cost, and high leaching rate, when compared with the conventional preparation of CaSnO3 or treatment of tin anode slime.